(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The objective of the research is to recognize sensual and emotional related to pain in blood cancer patients, and showing the differences according to sex on theses sensual and emotional expressions. QDSA Saint-Antoine scale was used to measure the sensual and emotional verbal expressions. 42 patients with blood cancer (Lymphoma and Leukimia), outside patients and hospitalized in Tishreen university hospital, oncology department, in Lattakia city were reviewed, (22) cases of female patients and (20) cases of male patients, aged between (40 and 65) The results show that cancer patients use rich words to describe theirpain, there are similarities and differences in sensual and emotional used for the verbal expression of pain in patients of both sexes, also there are sensual and emotional expressions that are not used or seldom used by patients. There is no difference between sexes in number, deepness and intensity in choosed words.